A metáfora da noite escura no itinerário espiritual de São João da Cruz (The metaphor of the dark night in spiritual journey of São João da Cruz) - DOI: 10.5752/P.2175-5841.2012v10n27p779 - Oliveira, Cleide Maria de (HORIZONTE - Revista de Estudos de Teologia e Ciências da Religião, 2012)
A imagem da noite é uma constante em diversas tradições místicas, estando associada à necessidade, expressa pela mística apofática, de transcender às imagens, ao conhecimento e ao nome de Deus, bem como a um método ascético que conduziria a uma experiência que não sendo sensível ou inteligível, não é catalogável pelo nosso sistema de cognição. A noite será uma das imagens mais poderosas e de maior expressividade na poesia de São João da Cruz, representante da mística ibérica do séc. XVI. Uma imagem negativa que nos fala de um processo de negação gradual e progressivo que avança até um ponto limite que onde reste a afirmação absoluta do Nome divino. O artigo pretende, pela análise dos poemas Cântico espiritual e Noite escura, ensaiar algumas conjecturas sobre o significado da metáfora noite escura em São João da Cruz e no discurso místico em geral. Palavras-chaves: São João da Cruz. Poesia mística. Cântico spiritual. Noite escura. Abstract: The image of the night is a constant in various mystical traditions, and it is generally related to the need, expressed by the mystical apophatic, of transcending the images, the knowledge, and the name of God. Such image is also comprehended as an ascetic method which would lead to an experience that is neither sensible nor intelligible, and because of that it is not understandable by our system of cognition. The night is one of the most powerful and expressive image in the poetry of São João da Cruz, a representative poet of the Iberian mystical poetry of the nineteenth century. The metaphor of the night is a negative image that speaks us of a process of gradual and progressive denial that moves toward a tipping point where the absolute affirmation of the Divine Name remains. The paper develops, through the analysis of the poems “Spiritual Chant” and “Dark Night”, some conjectures about the meaning of the dark night metaphor in São João da Cruz and in the mystical discourse as a whole Key-words: São João da Cruz. Mystical poetry. Spiritual Chant. Dark Night.